The legend : the Bessie Coleman story - Doolittle, Gardner; Walker, Aneva
In 1921, a young woman arose from the poverty of the Texas cotton fields. She captured the hearts of the American Black population, teaching them to overcome not only the racial barriers of the time but also the barriers within themselves. She dared to dream, and she challenged them to do so as well. Her name was Bessie Coleman. And, for Bessie Coleman, the sky was the limit ... The Legend: The Bessie Coleman Story presents the story of a renowned young woman of vision and courage who, despite the persistent threats of racism, simply refused to compromise herself, her principles, and her race!